2019
DOI: 10.1002/csr.1875
|View full text |Cite
|
Sign up to set email alerts
|

Embedding corporate sustainability: An empirical analysis of the antecedents of organization citizenship behavior

Abstract: The relation between organizational citizenship behavior (OCB) and the performance of both safety and environmental management systems has led researchers to investigate the drivers of safety-specific and environmental-oriented OCB. However, although the management of environmental and safety issues is often fully integrated into organizational and managerial practice, a holistic perspective of the drivers of health, safety, and environmental (HSE)-oriented OCB is still lacking. Thus, the aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 84 publications
(148 reference statements)
1
28
2
2
Order By: Relevance
“…First of all, the role of top management support emerges as crucial in several phases of the 4Is model. Besides a generic support, it is important to build a visionary leadership which is able to increase employee empowerment and trigger the proactive behavior that is fundamental for making effective the transition from an I-phase to another (Testa et al, 2020). The role of employees is determinant in this process.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…First of all, the role of top management support emerges as crucial in several phases of the 4Is model. Besides a generic support, it is important to build a visionary leadership which is able to increase employee empowerment and trigger the proactive behavior that is fundamental for making effective the transition from an I-phase to another (Testa et al, 2020). The role of employees is determinant in this process.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…We find that from a company perspective, the following aspects can be divided into internal issues and external issues. As internal issues, previous research has focused on: Employment and the role of organisation citizenship behaviour in embedding sustainability (Boiral, 2009; Testa, Boiral, & Heras‐Saizarbitoria, 2018; Testa, Todaro, Gusmerotti, & Frey, 2020); Managerial and board issues in defining CSR policies (Zaid, Abuhijleh, & Pucheta‐Martínez, 2020); Cultural factors for enhancing sustainable development (Baumgartner, 2014; Sannino, Lucchese, Zampone, & Lombardi, 2020). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The path toward sustainability requires changes in business models, appropriate technologies, operation processes, organizational forms, and performance objectives (Sharma & Henriques, 2005; Testa, Todaro, Gusmerotti, & Frey, 2020). Despite the considerable management complexity, the empirical investigation has shown that some SMEs are strongly committed to the development of green innovations (Klewitz & Hansen, 2011; Noci & Verganti, 1999).…”
Section: Theory and Hypothesismentioning
confidence: 99%